The Role of Pidie State Special School in Assisting Children with Special Needs in Pidie District - Dara Maisun; Inayatillah; Musdawati (Winaya Inspirasi Nusantara Foundation, 2021)
Children with special needs, known as ABK, are children who are educated to train and increase their potential. Special special schools play a role in providing assistance in understanding the situation that occurs around ABK through religious education assistance to form good character and assistance through the development of existing skills in ABK. The research aims to find out the role of SLBN Pidie in assisting children with special needs in Pidie Regency with a qualitative approach, collecting data through observation, interviews, and documentary study techniques, and completing the results of the research the author also uses literature review. The results of this study show that the role of SLBN Pidie in assisting children with special needs has not been running in accordance with the procedure, namely: (1) the number of general teachers who teach at SLBN Pidie, (2) the mixing of students with various disabilities in one class due to lack of facilities, (3) the absence of parental involvement in the mentoring process carried out at school. Researchers suggest that schools often conduct training for SLBN Pidie teachers to improve teacher competence in the education of children with special needs.